STRATEGI AKTIF PASIF DALAM OPTIMALISASI PORTOFOLIO SAHAM INDEKS LQ-45 - Ibnu Khajar (Jurnal Keuangan dan Perbankan, 2011)
The objective of investors to invest their money in the stock exchange was to maximize return although theywere subject to constraints, primarily risk. Return was the motivating force in the investment process. It was thereward for undertaking the investment. To overcome and lesson the risk, an investor needed to make diversificationthrough the formation of portfolio. The aim of this research was to know the return and risk from theactive and passive strategy in the stocks of LQ45, for 6 months periods, August 2009 until January 2010. Theactive strategy used the single index model and passive used the LQ45 share itself. The results of this researchindicated that active strategy (single index model): return portfolio was 5.43% and risk was 4.03%. Passivestrategy (following the index): return portfolio was 2% and risk was 3.5% and there was a linear relationshipbetween an assets risk and its required rate of return, the bigger the amount of return, the bigger the risk takenby investors or the reverse. The finding showed that between the two strategies, the return and risk of activestrategy as a whole was bigger than that of the passive strategy.